Changes in plant composition and diversity depending on previous and current management types in riparian forests at the confluence of rivers Morava and Dyje: phytocenological analysis at the gradients of light and moisture conditions - Hornych, Ondřej (Jihočeská univerzita, 2014)
Effects of various past and present management types on plant composition and diversity were examined in the species rich area at the confluence of rivers Morava and Dyje. A phytocenological analysis was supplemented with information about water and light conditions. Plant composition regarding residence time and invasive statuses was also examined for each management type.
Changes in plant composition and diversity depending on previous and current management types in riparian forests at the confluence of rivers Morava and Dyje: phytocenological analysis at the gradients of light and moisture conditions
Keywords: Soutok; Morava; Dyje; les; management; fytocenologie; Soutok; Morava; Dyje; March; Thaya; forest; management; phytocenology